Travelling home, Walkabout magazine and mid-twentieth-century Australia - Rolls, Mitchell, 1960-; Johnston, Anna, 1972- (Anthem studies in Australian literature and culture., 2016)
"Travelling Home' provides a detailed analysis of the contribution that the mid twentieth-century 'Walkabout' magazine made to Australia's cultural history. Spanning five central decades of the twentieth century (1934-1974), 'Walkabout' was integral to Australia's sense of itself as a nation. By advocating travel--both vicarious and actual--'Walkabout' encouraged settler Australians to broaden their image of the nation and its place in the Pacific region. In this way, 'Walkabout' explicitly aimed to make its readers feel at home in their country, as well as including a diverse picture of Aboriginal and Pacific cultures. Given its wide availability and distribution, together with its accessible and entertaining content, 'Walkabout' changed how Australia was perceived, and the magazine is recalled with nostalgic fondness by most if not all of its former readers. Drawing on interdisciplinary scholarship, Travelling Home engages with key questions in literary, cultural, and Australian studies about national identity and modernity. The book's diverse topics demonstrate how 'Walkabout' canvassed subtle and shifting fields of representation; as a result, this analysis produces complex and nuanced readings of Australian literary and cultural history"--